Reformulation of Institutional Relationship between the People’s Representative Council and the Corruption Eradication Commission - Rizki Ramadani (Faculty of Law, Universitas Lampung, 2021)
This study aims to reformulate the institutional relationships between legislative bodies and independent state institutions, by taking case studies of the House of Representatives (DPR) and the Corruption Eradication Commission (KPK). This research was conducted with a normative method using a conceptual and statutory approach. The results showed that the DPR-KPK institutional relationship can be formulated into authority relationship, supervisory relationship and financial relationship. In terms of the authority relationship, the principal-agent approach is used to place DPR as the principal whose duty is to support and provides the resources needed for the KPK as its agent. In this context, the KPK is the recipient of the task whose authority is within the subject of DPR. For the Supervision Relationship, The New Public Management Model (NPM) is used to initiate better supervision through the input and output control mechanism. Input control is carried out by DPR through the legislation and commisoner selection process, while output control is carried out based on accountability reports made by KPK. Thus, DPR is not allowed to intervene while the KPK exercise its duty. In terms of financial relationship, the DPR can regulate funding aspects for KPK through financial legislation. However, this budget politics must be adjusted to the needs and workload in carrying out KPK duties.